2012
DOI: 10.1128/mcb.01011-12
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF) Binding Protein 2 Functions Coordinately with Receptor Protein Tyrosine Phosphatase β and the IGF-I Receptor To Regulate IGF-I-Stimulated Signaling

Abstract: Insulin-like growth factor I (IGF-I) is a mitogen for vascular smooth muscle cells (VSMC) and has been implicated in the devel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 55 publications
(58 reference statements)
3
93
1
Order By: Relevance
“…2), mediates the binding of IGFBP-2 to the cell surface receptor protein tyrosine phosphatase β (RPTPβ) (Fig. 3 left), an event leading to inhibition of the RPTPβ phosphatase activity (Shen et al 2012). An IGFBP-2 modulates IGFs bioavailability to their receptors, with involvement of specific IGFBP-2 protease.…”
Section: Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…2), mediates the binding of IGFBP-2 to the cell surface receptor protein tyrosine phosphatase β (RPTPβ) (Fig. 3 left), an event leading to inhibition of the RPTPβ phosphatase activity (Shen et al 2012). An IGFBP-2 modulates IGFs bioavailability to their receptors, with involvement of specific IGFBP-2 protease.…”
Section: Ii)mentioning
confidence: 99%
“…3 IGF-dependent and IGF-independent action), including IGFBP-2 interactions at the cell surface (Russo et al 1995(Russo et al , 2005Shen et al 2012;Kawai et al 2011;DeMambro et al 2012) (Fig. 3) and intracellular / nuclear (Terrien et al 2005;Miyako et al 2009;Azar et al 2011Azar et al , 2014 (Fig.…”
Section: I)mentioning
confidence: 99%
“…However, we did not investigate the role of heparin-binding domain (HBD) in IGFBP-2 in our study. IGFBP-2 contains two HBDs, localized in the linker (HBD1) and C-terminal regions (HBD2), which are important for its binding to receptor protein tyrosine phosphatase β (RPTPβ) in regulating IGF-1 signalling (Shen et al 2012). In addition, integrin-mediated action of IGFBP-2 may contribute to the process of EPC homing to the injury site, which may be addressed through in vivo studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, IGFBP2 was shown to bind to the proteoglycan receptor protein tyrosine phosphatase b via the linker-HBD independent of IGF1 binding. This binding in turn enhanced IGF1-stimulated vascular smooth muscle cell migration and proliferation (Shen et al 2012).…”
Section: Discussionmentioning
confidence: 99%